The evolution of the political representation of African communities in DSWA/SWA/Namibia - Jan Klíma (Modern Africa, 2014)
The Republic of Namibia has an extremely complex composition of its population. Bantu nations, Khoisan groups, mixed communities and people of European origin create a political problem of how all those society segments can be represented in the national decision making process in a just and satisfactory way.